TRAIN THE TRAINER: HOW TO PREPARE A MEDICAL TEACHER “FROM SCRATCH” IN UKRAINE - Iurii Kuchyn; Kateryna Bielka; Lesya Lymar (Romanian Journal of Oral Rehabilitation)
"Aim of the study. The study aims to define basic directions in the medical teachers training in Ukraine, analyze the classical and modern clinical teaching approaches, and to define possible future of the medical teachers’ education in Ukraine. Methods. Literature review, descriptive analysis of academic performance and satisfaction of medical teachers in the Bogomolets NMU. Results. In Ukraine, the training of medical teachers lies within the domain of medical schools (universities), by training the medical graduates, medical PhDs and prominent clinicians to teach the others. If previously preference was given to the tutors with pedagogical education, now all medical teachers are the medical graduates who are taught how to teach by medical schools. The analysis of the academic performance at the Bogomolets NMU teacher training courses, both classical (N=400), and those under the European supervision(N=29) showed high rates of academic performance, as well as high satisfaction level of the trainees. The courses are focused at the clinical reasoning, simulation, medical classroom interaction, immersion, AI in medicine, etc. In order to improve the quality of teaching and seek for the new gifted medical teachers, the teaching component is going to be introduced into the curriculum of medical specialties as an indispensable component of their training. Conclusions. A good medical teacher is a clinician who possesses both clinical knowledge and skills, and the skills of educating the others. Such teachers in Ukraine are brought up during their undergraduate education, PhD studies, and their skills are improved by continuous professional education courses, provided by a certain medical school ( University). "